Answer: (7, 0)
Explanation:
We have the system of equations:
9*x - y = 63
x = y + 7
We can see that the "x" is isolated in the second equation, then we can replace it in the first equation to get:
9*x - y = 63
9*(y + 7) - y = 63
Now we have an equation that only depends on one variable, so we can solve it:
9*y + 63 - y = 63
8*y + 63 = 63
8*y = 63 - 63 = 0
y = 0/8 = 0.
Now we know the value of y, we can replace this in one of the initial equations to find the value of x, i will replace this in the second equation:
x = y + 7 = 0 + 7 = 7
Then the point that is a solution for the system of equations is (7, 0)